BACON’S SOCIO EPISTEMIC-TECNOLOGICAL UTOPIA. THE NEW ATLANTIS - Solano Villarreal, Diana (2017)
This article examines the position F. Bacon about the utopia of The New Atlantis, from the latter and Novum Organum, The Instauratio Magna and Wisdom of selfish author, from the perspective-colonial modernity / coloniality, specifically theory Bipolar Modernity Dr. Bernal Herrera. This explains what we believe the true characteristics of the utopia of Francis Bacon.